Pattern of Poisoning Cases in a Tertiary Care Centre in South India - An Observational study (Medico Legal Update, 2020)
Poison is any substance which when administered, inhaled or ingested is capable of causing deleteriouseffects on the human body. This prospective study was carried out involving 353 cases of poisoning admittedin Sri Ramachandra Medical College & Research Institute Porur, Chennai, during the period of June 2014-June 2015. The demographic details were acquired from the patient, relatives, friends or the investigatingofficer and by going through the medical records and the inquest report. In the current study the maximumcases were in the age group of 20-29 years and the incidence decreased as the age increases and it wasevident that the incidence of poisoning is more in case of females when compared to males. The material ofmaximum abuse was T.Alprazolam (10.8%), followed by Rat Killer poison (9.6%), and followed by SnakeStrike (8.8%), Organo Phosphorus Poisoning (8.5%), and Multiple Tablet Overdose (8.2%). 78% consumedpoison intentionally and are suicidal in nature, as no cases of homicidal poisoning were reported in the studygroup, rest of the 22% of cases, were of accidental in nature. Mortality wise analysis showed that dead casescount 13 in number which accounts to 3.5% of all poisoning cases.